CAPITAL WORKING ANALYSIS IN THE COMPANY (CASE STUDY AT PT. ANEKA TAMBANG TBK. YEAR 2015-2019) - Irvan Yoga Pardistya (STKIP Singkawang, 2020)
Working Capital is a comparison ratio in the company's financial management. This ratio compares income to current assets minus current Liabilities. PT. Aneka Tambang Tbk is one of the mining companies that performs well on the Indonesia Stock Exchange (IDX) because it is one of the LQ45 companies. In this research, PT. Aneka Tambang Tbk is the object of research. The unit of analysis is the Company's 2015-219 Financial Statements. Then the research methodology uses a quantitative descriptive approach with purposive sampling technique. The results of the discussion in the research of PT. Aneka Tambang Tbk experienced had decreased in income from 2015 to 2016 however, it rose up in 2016-2019. The increase from year to year is almost 100% from 2016 to 2018 and has increased 3 (three) times in the calculation. Thus, the company's performance is categorized as good and positive.